Effects of Different Types of Surfactant Treatments on the Electromechanical Properties of Multiwalled Carbon Nanotubes Decorated Electrospun Nanofibers - Sanli, Abdulkadir; Cinfer, Sule Pinar; Yoruc, Afife Binnaz Hazar (E.U. Printing and Publishing House, 2024)
Carbon nanotubes (CNTs) have a strong tendency to form agglomeration due to van der Waals interactions, which hinders their practical utilization. Therefore, an effective and stable dispersion of CNTs in a surfactant based solvent is very important for the realization of CNTs based nanocomposites in various applications. In this paper, influence of different types of surfactant on the electromechanical properties of multiwalled carbon nanotubes (MWCNTs) decorated electrospun thermoplastic polyurethane (TPU) nanofibers were investigated by UV-VIS spectroscopy, zeta potential, FT-IR analysis, scanning electron microscopy (SEM) and uniaxial tensile strain sensing. Obtained results suggest that type of surfactant has not only effecting the dispersion level of CNTs but also has a significant influence on the electromechanical properties of CNTs decorated elecrospun CNTs/TPU nanofibers. The results of the present study provide new insights into the design and tailoring the electromechanical properties of CNTs decorated electrospun nanofibers.
Keywords: Multiwalled carbon nanotubes; thermoplastic polyurethane; electrospinning; nanofibers; STRAIN SENSORS; DISPERSION; FUNCTIONALIZATION; NANOCOMPOSITES; SYSTEM; FILMS; Materials Science